2021
DOI: 10.1038/s41562-021-01141-5
|View full text |Cite
|
Sign up to set email alerts
|

Cortical recycling in high-level visual cortex during childhood development

Abstract: Human ventral temporal cortex (VTC) contains category-selective regions that respond preferentially to ecologically-relevant categories such as faces, bodies, places, and words, which are causally involved in the perception of these categories. How do these regions develop during childhood? We used functional MRI to measure longitudinal development of category-selectivity in school-age children over 1 to 5 years. We discovered that from young childhood to the teens, face- and word-selective regions in VTC expa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 61 publications
8
82
0
Order By: Relevance
“…The RH dominance for face-selective neural responses is present from the start of the study and, while impressive changes occur at the VWFA location for words, is remarkably stable across testing sessions in full agreement with a fair evaluation of the adult study of Dehaene et al (2010). Based on these observations, Dehaene-Lambertz et al (2018) suggest that new visual categories, such as letter strings, invade only weakly specified cortex, while leaving face-selective cortical responses unchanged (see also the most recent fMRI study of Nordt et al, 2021). Unless one can demonstrate that further expansions of category-selective responses to faces at later developmental stages are specifically blocked in the LH, increasing RH dominance of face recognition even further, such findings speak directly against even a weak version of the reading-LNC hypothesis.…”
Section: Summary Of Children Studiessupporting
confidence: 74%
See 1 more Smart Citation
“…The RH dominance for face-selective neural responses is present from the start of the study and, while impressive changes occur at the VWFA location for words, is remarkably stable across testing sessions in full agreement with a fair evaluation of the adult study of Dehaene et al (2010). Based on these observations, Dehaene-Lambertz et al (2018) suggest that new visual categories, such as letter strings, invade only weakly specified cortex, while leaving face-selective cortical responses unchanged (see also the most recent fMRI study of Nordt et al, 2021). Unless one can demonstrate that further expansions of category-selective responses to faces at later developmental stages are specifically blocked in the LH, increasing RH dominance of face recognition even further, such findings speak directly against even a weak version of the reading-LNC hypothesis.…”
Section: Summary Of Children Studiessupporting
confidence: 74%
“…While the authors interpreted this observation in favor of the lateralized neural competition hypothesis, from our understanding, it actually goes against the view that the emergence of LH lateralization for words would increase RH lateralization for faces. Finally, in another fMRI study using a classifier approach, there was no relationship between the word classification in the left VOTC and the face classification in the right VOTC, or between their laterality indexes, suggesting independent development of category-selective neural responses to faces and written words in this region (Nordt et al 2021).…”
Section: Correlations Between Face-and Word-selective Neural Responsesmentioning
confidence: 89%
“…These data have prompted a reexamination of the neuronal recycling hypothesis by suggesting that word-selective responses do not compete for cortical territory with other visual categories. However, a recent longitudinal study revealed that limb-selective regions in VOTC lose cortical territory to word-selective regions over the course of elementary school 18 .…”
Section: Figurementioning
confidence: 99%
“…Particularly, we found two distinct visual clusters along the medial-lateral axis, which captured the central-peripheral organization of ventral visual system (Grill-Spector and Weiner, 2014;Hasson et al, 2002;Levy et al, 2001;Wiesel, 1982). Apart from the border of two medial-lateral clusters, the lateral area become more face-selective while the medial area is specialized in processing scene and buildings later in life (Nordt et al, 2021), and thereby our observation suggests the innate scaffold already established at birth for subsequent experience-dependent modification in ventral visual cortex Livingstone, 2021, 2017). Furthermore, the connections among the ventral visual cortex have developed during this early stage.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies reported the coupling between cortical myelination and face processing, suggesting an experience-dependent development of visual cortical microstructure in later life (e.g. 5-12 years old; Nordt et al, 2021). We found that in the early stage, CM primarily correlated with the prenatal time (GA at birth) but not the extrinsic experience, suggesting that the early cortical myelination might be determined the endogenic growth.…”
Section: Discussionmentioning
confidence: 88%